Effect of lubricants on the properties of tablets compressed from varied size granules - Ellen Hackl; Irina Ermolina; Elena Kabova (University of Huddersfield Press, 2023)
Magnesium stearate (MgSt) is one of the most widely used solid lubricants in oral solid dosage forms. However, MgSt can negatively impact the tablets, decreasing their mechanical properties and lengthening disintegration/dissolution times. The aim of the present study was to compare the effect of MgSt and Sodium Stearyl Fumarate (SSF) lubricants on the physical characteristics of immediate release caffeine tablets compressed using granules of different sizes. Overall, the results demonstrate that using SSF as a lubricant significantly enhances tablet mechanical strength and reduces disintegration/wetting times for all granule sizes used to compress tablets. With smaller granules, SSF tends to be more effective. Over-lubrication with SSF leads to a decrease in tablet hardness as well, though to a significantly lesser extent than over-lubrication with MgSt.